Banking impacts of the granting of credits for the residential construction at the municipality the Ox Arrives (Original) (REDEL. Revista Granmense de Desarrollo Local, 2021)
The residential construction constitutes a maximum priority in the strategy of local development of the municipality the Ox Arrives. The transformations attained at the territory as from the assignment of bank credits are numerous enter (2012 – 2020). The investigation responds to the problem related with:  Which ones are the principal banking impacts of the granting of credits for the residential construction at the municipality does the Ox Arrive? Having like objective: Reflecting about the impacts obtained by the granting of credits banking for the residential construction through Ahorro's Popular Bench (BPA) at the mentioned locality. They approach the referent more important theoreticians of the investigation in the realized study and himself make visible the fundamental changes in the habitational bottom.  The assessment of the successful results his applicability increasing the power of the boyarribenses's quality of life that way passes as from the application of the pre-experiment, being feasible and effective.
Keywords: residential construction; local development; bank credits; habitational bottom